Produksi Konten Islami Dalam Strategi Engagement Melalui Media Online Harian Disway - Magdalena Asri; Doan Widhiandono (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Disway Daily is one of the convergent mass media that focuses on news and online articles and e-papers. Currently, the reader of the rubric is dominated by football fans, as there are many articles about the results of football matches and other sports. The month of Ramadan, the holy month in Islam, not only reflects a time for fasting, but also marks a period of introspection, reflection, and blessing for Muslims around the world. Online media has a great responsibility to convey appropriate, in-depth, and inspirational information related to Ramadan. With that, the Ramadan rubric comes as a platform that presents the festivities and wisdom of Ramadan to readers in an interesting and meaningful way. The Ramadan rubric is important because it facilitates a better understanding of the rituals and values associated with this holy month. Through this rubric, online media can highlight various aspects, including specific rituals performed by Muslims, as well as fasting laws based on the teachings of the Qur'an and Hadith. In building this rubric, it is important to ensure that the content presented matches the needs and interests of readers, and inspires them to live Ramadan with passion and blessings. Keywords: Disway Daily, Online Media, Ramadan Rubric, Ramadan Rubric, Islamic Content, Ramadan Fasting